2016
DOI: 10.1051/matecconf/20168106002
|View full text |Cite
|
Sign up to set email alerts
|

Lean Supply Chain Planning: A Performance Evaluation through Simulation

Abstract: Abstract. Nowadays companies look more and more for improving their efficiency to excel in the market. At the same time, the competition has moved from firm level to whole supply chain level. Supply chain are very complex systems and lacks of coordination among their members leads to inefficiency. Supply chain planning task is to improve coordination among supply chain members. Which is the best planning solution to improve efficiency is an open issue. On the other hand, Lean approach is becoming more and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Unit cost of manufacturing decreases drastically when value stream mapping (VSM) is used in LSC environments (Wee and Wu, 2009). Likewise, the use of Kanban cards and pull flow systems in a JIT SC reduces manufacturing costs (Rossini and Portioli-Staudacher, 2016). Also, generally speaking, integrated inventory management reduces inventory-related costs (Hooshang, 2010) and, especially, the cost of preparing JIT purchase orders (Parveen and Rao, 2009;Hooshang, 2010), JIT distribution transport and delivery costs (Wang et al, 2004) and JIT delivery transport costs (Chen and Sarker, 2010) achieves higher stock turnover while minimising inventory (Rossini and Portioli-Staudacher, 2016).…”
Section: Lean Supply Chain Management-focal Firm Efficiency Relationshipmentioning
confidence: 99%
“…Unit cost of manufacturing decreases drastically when value stream mapping (VSM) is used in LSC environments (Wee and Wu, 2009). Likewise, the use of Kanban cards and pull flow systems in a JIT SC reduces manufacturing costs (Rossini and Portioli-Staudacher, 2016). Also, generally speaking, integrated inventory management reduces inventory-related costs (Hooshang, 2010) and, especially, the cost of preparing JIT purchase orders (Parveen and Rao, 2009;Hooshang, 2010), JIT distribution transport and delivery costs (Wang et al, 2004) and JIT delivery transport costs (Chen and Sarker, 2010) achieves higher stock turnover while minimising inventory (Rossini and Portioli-Staudacher, 2016).…”
Section: Lean Supply Chain Management-focal Firm Efficiency Relationshipmentioning
confidence: 99%
“…Also, the study by Ruiz-Benitez et al (2019) identified eight LSCM practices that reduced costs. The use of lean manufacturing techniques such as Kanban cards and pull flow systems contributes to cost reduction (Rossini and Portioli-Staudacher, 2016). Similarly, reducing the inventory level is linked to inventory cost reduction (Hooshang, 2010).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Authors compared two different supermarket configurations for the integration of information and material flows, aiming to understand scientific implications and the applicability of such kind practice to realistic cases (Frazzon et al, 2017). A similar simulation work carried out by Rossini and Portioli Staudacher, analysed in-depth the impact of implementing Pull and Flow principles in SCP and compared it with other SCP models in a multi-product SC (Rossini & Staudacher, 2016).…”
Section: Lean Management-based Scp Model (Lean-p)mentioning
confidence: 99%